Integrated conductive ceramic membrane and preparation method and application thereof

Through the co-precipitation-calcination-mixed ball milling-hydraulic press-calcination, an integrated conductive ceramic film was prepared, which solved the problems of complex preparation process of the existing conductive ceramic film and the easy fall off of the conductive coating, and achieved efficient and reliable conductivity Ceramic membrane preparation.

CN119430907AActive Publication Date: 2025-02-14ORDOS SHENGYUAN WATER GRP CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411570243.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

The preparation process of existing conductive ceramic films is complex, the filmmaking efficiency is low, and the conductive coating is prone to fall off, resulting in poor reliability.

Method used

The integrated conductive ceramic film is prepared by the method of co-precipitation-calcination-mixed ball mill-hydraulic press-calcination. The conductive powder is obtained by mixing the tin source, metal dopant, alkali reagent and organic solvent for co-precipitation reaction. And through hydraulic pressing and multiple calcination, a tightly bonded conductive ceramic film is formed.

Benefits of technology

It has achieved simplified preparation process, reduced generation difficulty, improved film making efficiency, and avoided the problem of conductive coating falling off, improving the reliability and conductive properties of the film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430907A_ABST
    Figure CN119430907A_ABST
Patent Text Reader

Abstract

The invention provides an integrated conductive ceramic membrane as well as a preparation method and application thereof, and belongs to the technical field of sewage treatment. According to the invention, a Sn source and a metal dopant are used as raw materials, and a method of coprecipitation, calcination, mixed ball milling, hydraulic pressing and calcination is adopted, so that the ceramic membrane has conductivity, the integrated conductive ceramic membrane is directly prepared, and the preparation of the integrated conductive ceramic membrane is realized. According to the method disclosed by the invention, the whole ceramic membrane has electrical conductivity, the problem that the conductive coating falls off in a coating method can be avoided, the preparation process can be simplified, the generation difficulty can be reduced, and the membrane preparation efficiency can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sewage treatment, and in particular to an integrated conductive ceramic membrane and a preparation method and application thereof. Background Art

[0002] The preparation of existing conductive ceramic membranes is mainly based on the coating method, which includes but is not limited to: directly spraying conductive materials on ordinary ceramic membranes, immersing ordinary ceramic membranes in conductive material solutions, and inserting conductive materials into the pores of ordinary ceramic membranes. However, the process of the coating method is usually not simple. It not only requires certain treatment of the conductive material, but also requires pretreatment of the ordinary ceramic membrane. The process is complicated and the film-making efficiency is low. It is important that the conductive part of the conductive ceramic membrane prepared by the coating method is separated from the ceramic membrane itself, and there is a problem that the conductive coating or material is easy to fall off. If the conductive material falls off during the wastewater treatment process, it will not only reduce the treatment effect, but also greatly shorten the life of the membrane. Therefore, the reliability of this type of conductive ceramic membrane is poor. Summary of the invention

[0003] The object of the present invention is to provide an integrated conductive ceramic membrane and a preparation method and application thereof. The integrated conductive ceramic membrane has conductivity as a whole, which can not only avoid the problem of conductive coating falling off in the coating method, but also simplify the preparation process and reduce the difficulty of production.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a method for preparing an integrated conductive ceramic film, comprising the following steps:

[0006] A tin source, a metal dopant, an alkali reagent and an organic solvent are mixed to perform a coprecipitation reaction to obtain a precipitated product;

[0007] The precipitation product is subjected to a first calcination to obtain a conductive powder;

[0008] The conductive powder, the additive and the alcohol solvent are mixed and ball-milled to obtain nano conductive powder;

[0009] Hydraulically pressing the nano-conductive powder to obtain a pressed tablet;

[0010] The pressed sheet is subjected to a second calcination to obtain an integrated conductive ceramic membrane;

[0011] The metal element in the metal dopant includes Sb, Co, Ni, La, Mn, Al or Zn.

[0012] Preferably, the tin source includes SnCl4 or SnCl2; and the alkaline reagent includes aqueous ammonia.

[0013] Preferably, the metal dopant includes SbCl3, CoCl2, NiCl2, LaCl3, MnCl2, AlCl3 or ZnCl2; the molar amount of the metal element in the metal dopant is 0 to 12% of the Sn element in the tin source and is not 0.

[0014] Preferably, the pH of the coprecipitation reaction is 8.0-10; the temperature is 60-100° C., and the time is 2-6 hours.

[0015] Preferably, the temperature of the first calcination is 500-800° C., and the time is 1-4 hours.

[0016] Preferably, the auxiliary agent includes aluminum oxide, zirconium oxide or silicon carbide; the mass of the auxiliary agent is 0 to 60% of the mass of the conductive powder; the time of the mixed ball milling is 1 to 3 hours; the pressure of the hydraulic pressing is 3 to 9 MPa, and the stabilization time is 40 to 80 seconds.

[0017] Preferably, the second calcination temperature is 900-1200° C. and the time is 1-4 hours.

[0018] The present invention provides an integrated conductive ceramic membrane prepared by the preparation method described in the above technical solution, and uses a cross-flow electrochemical coupled membrane separation device to treat sewage.

[0019] Preferably, the cross-flow electrochemical coupled membrane separation device includes a raw water tank 1, a diaphragm pump 2, a power supply 3, an electrolysis-filtration reactor 4, a water production tank 5, a reflux water regulating valve 8 and a water production regulating valve 9, wherein the raw water tank 1, the diaphragm pump 2, the electrolysis-filtration reactor 4 and the water production tank 5 are connected in sequence; the power supply 3 is connected to the electrolysis-filtration reactor 4; a conductive ceramic membrane 6 and a cathode 7 are arranged in the electrolysis-filtration reactor 4; the reflux water regulating valve 8 is arranged in the pipeline between the electrolysis-filtration reactor 4 and the raw water tank 1, and the water production regulating valve 9 is arranged in the pipeline between the electrolysis-filtration reactor 4 and the water production tank 5; the conductive ceramic membrane 6 is the integrated conductive ceramic membrane described in the above technical scheme; the integrated conductive ceramic membrane serves as an anode.

[0020] The present invention provides the application of the integrated conductive ceramic membrane described in the above technical solution in sewage treatment.

[0021] The present invention provides a method for preparing an integrated conductive ceramic membrane, and adopts a co-firing method to prepare an integrated conductive ceramic membrane. The present invention uses Sn source and metal dopant as raw materials, and adopts a co-precipitation-calcination-mixed ball milling-hydraulic pressing-calcination method to make the ceramic membrane have the ability to conduct electricity and directly prepare an "integrated" conductive ceramic membrane, thereby realizing the preparation of an integrated conductive ceramic membrane, and at the same time giving the membrane conductive properties and membrane separation efficiency. The "integrated" described in the present invention is different from the conductive material in the coating method being independent of the ceramic membrane body, wherein "integrated" refers to the conductive powder material being tightly combined to jointly constitute the entire conductive ceramic membrane, rather than a load-modified conductive layer. The method of the present invention enables the ceramic membrane to have conductivity as a whole, which not only avoids the problem of conductive coating shedding in the coating method, but also simplifies the preparation process, reduces the difficulty of generation, and improves the efficiency of film making.

[0022] The present invention uses the integrated conductive ceramic membrane as both an anode and a separation membrane for the treatment of oily wastewater, and the integrated conductive ceramic membrane has an electrocatalytic effect as a whole. In the application process, a cross-flow electrochemical coupling membrane separation device is used, with a conductive ceramic membrane as an anode and Al (or Fe) as a cathode, and a membrane filtration process is performed synchronously during the power-on process. The integrated conductive ceramic membrane effectively removes pollutants and dirt on the membrane surface under the action of electro-oxidation generated by voltage excitation, in-situ electrogenerated ROS, electrostatic action, electrogenerated bubbles, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The SEM images of the integrated Sb-doped SnO2 conductive ceramic film prepared in Example 1, (a) to (d) are SEM images under 0.5k times, 6k times, 50k times, and 100k times magnification conditions, respectively;

[0024] Figure 2 Schematic diagram of the contact angle of the integrated Sb-doped SnO2 conductive ceramic film prepared in Example 1;

[0025] Figure 3 The cyclic voltammetry curve of the integrated Sb-doped SnO2 conductive ceramic film prepared in Example 1;

[0026] Figure 4 This is the XRD pattern of the integrated Sb-doped SnO2 conductive ceramic film prepared in Example 1;

[0027] Figure 5 This is the XPS graph of the integrated Sb-doped SnO2 conductive ceramic film prepared in Example 1;

[0028] Figure 6This is a diagram of the electrochemical coupled membrane separation treatment device used in the test example, wherein: 1-raw water tank; 2-diaphragm pump; 3-power supply; 4-electrolysis-filtration reactor; 5-water production tank; 6-conductive ceramic membrane; 7-cathode; 8-reflux water regulating valve; 9-water production regulating valve. DETAILED DESCRIPTION

[0029] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.

[0030] The present invention provides a method for preparing an integrated conductive ceramic film, comprising the following steps:

[0031] A tin source, a metal dopant, an alkali reagent and an organic solvent are mixed to perform a coprecipitation reaction to obtain a precipitated product;

[0032] The precipitation product is subjected to a first calcination to obtain a conductive powder;

[0033] The conductive powder, the additive and the alcohol solvent are mixed and ball-milled to obtain nano conductive powder;

[0034] Hydraulically pressing the nano-conductive powder to obtain a pressed tablet;

[0035] The pressed sheet is subjected to a second calcination to obtain an integrated conductive ceramic membrane;

[0036] The metal element in the metal dopant includes Sb, Co, Ni, La, Mn, Al or Zn.

[0037] In the present invention, the tin source preferably includes SnCl4 or SnCl2; the alkaline reagent preferably includes ammonia water (mass concentration is preferably 22-25%), and the pH value is adjusted to the desired value using the alkaline reagent; the organic solvent is preferably ethanol, methanol or ethylene glycol; the concentration of the tin source in the organic solvent is preferably 0.5 mol / L (calculated as Sn ion concentration).

[0038] In the present invention, the metal dopant preferably includes SbCl3, CoCl2, NiCl2, LaCl3, MnCl2, AlCl3 or ZnCl2; the molar amount of the metal element in the metal dopant is preferably 0 to 12% of the Sn element in the tin source and is not 0, more preferably 1 to 9%, and further preferably 3 to 8%.

[0039] In the present invention, the tin source is preferably placed in an organic solvent, a metal dopant is added, an alkali reagent is added dropwise after stirring and mixing, and the desired pH is reached to carry out a coprecipitation reaction.

[0040] In the present invention, the pH of the coprecipitation reaction is preferably 8.0 to 10, more preferably 8.0; the temperature is preferably 60 to 100° C., more preferably 70 to 100° C.; the time is preferably 2 to 6 hours, more preferably 4 hours. The dissolved metal ions in the solution are precipitated together in the form of hydroxide precipitates.

[0041] After the coprecipitation reaction is completed, the present invention preferably uses a vacuum filter to filter, washes with pure water 5 times, dries, and grinds into powder to obtain a precipitated product, and the precipitated product is first calcined in a muffle furnace.

[0042] In the present invention, the temperature of the first calcination is preferably 500-800°C, more preferably 600-700°C, the time is preferably 1-4h, more preferably 2-3h; the heating rate to the temperature of the first calcination is preferably 5°C / min. The present invention converts the metal hydroxide precipitate formed by the coprecipitation reaction into the corresponding oxide through the first calcination, and substitution doping (Sb replaces the lattice position of Sn) occurs during the oxide generation process, and the doping element replaces the site of certain atoms in the matrix material, changing the conductivity and band structure of the material.

[0043] In the present invention, the auxiliary agent preferably includes aluminum oxide, zirconium oxide or silicon carbide; the mass of the auxiliary agent is preferably 0-60% of the mass of the conductive powder, more preferably 20-50%; the present invention utilizes the auxiliary agent to improve the mechanical strength of the integrated film and enhance the stability of the integrated film.

[0044] In the present invention, the alcohol solvent is preferably ethanol, and the medium used in the mixed ball milling is preferably zirconia ball milling beads. The mass ratio of the total mass of the conductive powder and the additive, and the mass ratio of the zirconia ball milling beads to the alcohol solvent is preferably 1:2:1; the time of the mixed ball milling is 1 to 3 hours, more preferably 2 hours.

[0045] After the mixed ball milling, the present invention preferably uses a centrifuge to centrifuge, removes the supernatant, and dries the obtained mixture in an oven at 105° C. for 12 hours to obtain nano conductive powder.

[0046] The present invention preferably places the nano-conductive powder into a circular tabletting mold and uses a hydraulic powder tabletting machine to perform hydraulic pressing. The present invention has no special limitation on the size of the tablets obtained by the hydraulic pressing, which can be adjusted according to actual needs. In the embodiment of the present invention, the tablets are specifically pressed into round tablets with a diameter of 30 mm and a thickness of 3 mm.

[0047] In the present invention, the pressure of the hydraulic pressing is preferably 3 to 9 MPa, more preferably 6 to 8 MPa, and the stabilization time is preferably 40 to 80 s, more preferably 60 s.

[0048] In the present invention, the temperature of the second calcination is preferably 900-1200°C, more preferably 1000-1200°C, the time is preferably 1-4h, more preferably 2-3h; the heating rate to the temperature of the second calcination is preferably 5°C / min. The present invention achieves effective bonding of particles and optimizes the microstructure of the material through the second calcination; provides sufficient energy to promote bonding and mutual penetration between particles; and at high temperatures, the diffusion rate of atoms or molecules of solid materials increases, which helps to reverse the reduction of free energy during sintering and promote the bonding of particles.

[0049] The present invention provides an integrated conductive ceramic film prepared by the preparation method described in the above technical solution.

[0050] The present invention provides an application of the integrated conductive ceramic membrane described in the above technical solution in sewage treatment, and uses a cross-flow electrochemical coupled membrane separation device to treat sewage.

[0051] In the present invention, Figure 6 As shown, the cross-flow electrochemical coupled membrane separation device includes a raw water tank 1, a diaphragm pump 2, a power supply 3, an electrolysis-filtration reactor 4, a water production tank 5, a reflux water regulating valve 8 and a water production regulating valve 9, wherein the raw water tank 1, the diaphragm pump 2, the electrolysis-filtration reactor 4 and the water production tank 5 are connected in sequence; the power supply 3 is connected to the electrolysis-filtration reactor 4; a conductive ceramic membrane 6 and a cathode 7 are arranged in the electrolysis-filtration reactor 4; the reflux water regulating valve 8 is arranged in the pipeline between the electrolysis-filtration reactor 4 and the raw water tank 1, and the water production regulating valve 9 is arranged in the pipeline between the electrolysis-filtration reactor 4 and the water production tank 5; the conductive ceramic membrane 6 is the integrated conductive ceramic membrane described in the above technical solution; the integrated conductive ceramic membrane serves as an anode.

[0052] The present invention has no particular limitation on the process of assembling the conductive ceramic membrane 6 and cathode 7 into the electrolysis-filtration reactor 4. The conductive ceramic membrane 6 and cathode 7 can be installed in a conventional container to form the electrolysis-filtration reactor 4 in a manner well known in the art.

[0053] In the present invention, the cathode 7 is preferably a Fe electrode or an aluminum electrode.

[0054] The present invention has no special limitation on the specific structure and connection process of each component in the cross-flow electrochemical coupled membrane separation device, and corresponding component pipelines well known in the art can be used for connection.

[0055] In the cross-flow electrochemical coupled membrane separation device described in the present invention, the outlet water of the raw water tank 1 is connected to the diaphragm pump 2, and the wastewater flows to the electrolysis-filtration reactor 4 under the pressure of the diaphragm pump 2, and is filtered out from the conductive ceramic membrane and enters the water production tank 5 under pressure drive; the water flow in the middle of the electrolysis-filtration reactor 4 is controlled by adjusting the reflux water regulating valve 8 to control the water volume of the reflux water, and the reflux water flows from the electrolysis-filtration reactor 4 to the raw water tank 1.

[0056] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0057] Example 1

[0058] Weigh 13.02565g (0.05mol) SnCl4 and dissolve it in 100mL ethylene glycol (i.e., the Sn ion concentration is 0.5mol / L), add 0.9124g (0.004mol) SbCl3 (the molar amount of Sb is 8% of Sn), and stir to mix; add ammonia water with a mass concentration of 25% so that the pH of the mixed solution is 8.0; increase the temperature of the water bath and keep the water bath at a constant temperature of 70°C for 4h; use a vacuum filter to filter the obtained mixture, wash it with pure water 5 times, dry it at 105°C for 12h, and grind it into powder; put the ground powder into a muffle furnace and heat it at 5°C / min, calcine it at 700°C for 2h, and cool it naturally to obtain a conductive powder;

[0059] According to the mass of aluminum oxide being 20% ​​of the mass of the conductive powder, the conductive powder and aluminum oxide are uniformly mixed to obtain a mixed powder, and the mixed powder: zirconium oxide ball milling beads: ethanol mass ratio is 1:2:1, and after ball milling for 2 hours, the mixture is centrifuged in a centrifuge, the supernatant is removed, and the mixture is dried in an oven at 105° C. for 12 hours to obtain a nano conductive powder;

[0060] Take 5.0g of nano-conductive powder and put it into a circular tablet pressing mold. Use a hydraulic powder tablet press to stabilize it at a pressure of 6MPa for 60s and press it into a disc with a diameter of 30mm and a thickness of 3mm; place it in a muffle furnace and heat it at 5℃ / min, keep calcining at 1200℃ for 2h, and cool it naturally to obtain an integrated Sb-doped SnO2 conductive ceramic film.

[0061] Example 2

[0062] Weigh 13.02565g SnCl4 and dissolve it in 100mL ethylene glycol (i.e., the Sn ion concentration is 0.5mol / L), add 0.06491g (0.00065mol) CoCl2 (the molar amount of Co is 1% of Sn), mix and stir; add ammonia water with a mass concentration of 25% so that the pH of the mixed solution is 8.0; increase the temperature of the water bath and keep the water bath at a constant temperature of 70°C for 4h; use a vacuum filter to filter the obtained mixture, wash it with pure water 5 times, dry it at 105°C for 12h, and grind it into powder; put the ground powder into a muffle furnace and heat it at 5°C / min, calcine it at 700°C for 2h, and cool it naturally to obtain a conductive powder;

[0063] According to the mass of aluminum oxide being 20% ​​of the mass of the conductive powder, the conductive powder and aluminum oxide are uniformly mixed to obtain a mixed powder, and the mixed powder: zirconium oxide ball milling beads: ethanol mass ratio is 1:2:1, and after ball milling for 2 hours, the mixture is centrifuged in a centrifuge, the supernatant is removed, and the mixture is dried in an oven at 105° C. for 12 hours to obtain a nano conductive powder;

[0064] Take 5.0g of nano-conductive powder and put it into a circular tablet pressing mold. Use a hydraulic powder tablet press to stabilize it at a pressure of 6MPa for 60s and press it into a disc with a diameter of 30mm and a thickness of 3mm; place it in a muffle furnace and heat it at 5℃ / min, keep calcining at 1200℃ for 2h, and cool it naturally to obtain an integrated Co-doped SnO2 conductive ceramic film.

[0065] Example 3

[0066] 13.02565g SnCl4 was weighed and dissolved in 100mL ethylene glycol (i.e., the Sn ion concentration was 0.5mol / L), and 0.50336g (0.004mol) MnCl2 (Mn molar amount was 8% of Sn) was added and mixed and stirred; 25% ammonia water was added dropwise to make the pH of the mixed solution 8.0; the temperature of the water bath was increased and kept at a constant temperature of 70°C for 4h; the obtained mixture was filtered using a vacuum filter, washed with pure water 5 times, dried at 105°C for 12h, and ground into powder; the ground powder was placed in a muffle furnace and heated at 5°C / min, calcined at 700°C for 2h, and cooled naturally to obtain a conductive powder;

[0067] According to the mass of aluminum oxide being 20% ​​of the mass of the conductive powder, the conductive powder and aluminum oxide are uniformly mixed to obtain a mixed powder, and the mixed powder: zirconium oxide ball milling beads: ethanol mass ratio is 1:2:1, and after ball milling for 2 hours, the mixture is centrifuged in a centrifuge, the supernatant is removed, and the mixture is dried in an oven at 105° C. for 12 hours to obtain a nano conductive powder;

[0068] Take 5.0g of nano-conductive powder and put it into a circular tablet pressing mold. Use a hydraulic powder tablet press to stabilize it at a pressure of 6MPa for 60s and press it into a disc with a diameter of 30mm and a thickness of 3mm; place it in a muffle furnace and heat it at 5℃ / min, keep calcining at 1200℃ for 2h, and cool it naturally to obtain an integrated Mn-doped SnO2 conductive ceramic film.

[0069] Comparative Example 1

[0070] Commercial porous alumina ceramic membrane (Anhui Tianling Technology Co., Ltd.; model: pore size 500 nm, thickness 4 mm, diameter 38 mm).

[0071] Comparative Example 2

[0072] 13.02565g SnCl4 was weighed and dissolved in 100mL ethylene glycol (i.e., the Sn ion concentration was 0.5mol / L) and mixed and stirred; 25% ammonia water was added dropwise to make the pH of the mixed solution 8.0; the temperature of the water bath was increased and the water bath was kept at a constant temperature of 70°C for 4h; the obtained mixture was filtered using a vacuum filter, washed with pure water 5 times, dried at 105°C for 12h, and ground into powder; the ground powder was placed in a muffle furnace and heated at 5°C / min, calcined at 700°C for 2h, and cooled naturally to obtain a conductive powder;

[0073] According to the mass of aluminum oxide being 20% ​​of the mass of the conductive powder, the conductive powder and aluminum oxide are uniformly mixed to obtain a mixed powder, and the mixed powder: zirconium oxide ball milling beads: ethanol mass ratio is 1:2:1, and after ball milling for 2 hours, the mixture is centrifuged in a centrifuge, the supernatant is removed, and the mixture is dried in an oven at 105° C. for 12 hours to obtain a nano conductive powder;

[0074] Take 5.0g of nano-conductive powder and put it into a circular tablet pressing mold. Use a hydraulic powder tablet press to stabilize it at a pressure of 6MPa for 60s and press it into a disc with a diameter of 30mm and a thickness of 3mm; place it in a muffle furnace and heat it at 5℃ / min, keep calcining at 1200℃ for 2h, and cool it naturally to obtain an integrated SnO2 conductive ceramic film.

[0075] Characterization and performance testing

[0076] Figure 1 The SEM images of the integrated Sb-doped SnO2 conductive ceramic membrane prepared in Example 1; (a) to (d) are SEM images at 0.5k times, 6k times, 50k times, and 100k times magnification, respectively. The ceramic membrane is made of spherical particles connected and stacked with each other and has rich porosity.

[0077] Figure 2Schematic diagram of the contact angle of the integrated Sb-doped SnO2 conductive ceramic film prepared in Example 1; it shows that the ceramic film has excellent hydrophilicity and the contact angle is 0°.

[0078] Figure 3 This is a cyclic voltammogram of the integrated Sb-doped SnO2 conductive ceramic membrane prepared in Example 1, indicating that the ceramic membrane has excellent electrochemical properties.

[0079] Figure 4 This is the XRD diagram of the integrated Sb-doped SnO2 conductive ceramic film prepared in Example 1; it can be seen that the conductive ceramic film only contains Sb-doped SnO2 and aluminum oxide, and there are no other strong peaks, indicating that the sample has very few impurities and is relatively pure.

[0080] Figure 5 This is the XPS graph of the integrated Sb-doped SnO2 conductive ceramic film prepared in Example 1; the presence of Al, Sn and Sb elements is confirmed.

[0081] Test Case

[0082] 1) The conductivity of different ceramic films was tested using the four-way probe resistance method. The results are shown in Table 1

[0083] Table 1 Conductive properties of conductive ceramic film materials of Comparative Examples 1-2 and Examples 1-3

[0084]

[0085] It can be seen from Table 1 that the modified conductive ceramic membrane material prepared by the present invention has excellent conductive properties, which are significantly better than the undoped integrated SnO2 ceramic membrane in Comparative Example 2.

[0086] 2) Conducting organic wastewater performance tests on conductive ceramic membrane materials in different cases:

[0087] The conductive ceramic membrane material was used as the anode and separation membrane, Al was used as the cathode, the initial membrane flux was controlled to be 400LMH, the electrolyte was 10mM Na2SO4, and the current density was 40mA / cm 2 , and the oily wastewater was treated, and the emulsified oil content in the wastewater was 2000 mg / L. The results are shown in Table 2.

[0088] Table 2 Removal effect of emulsified oil by different conductive ceramic membranes in wastewater treatment

[0089]

[0090] As shown in Table 2, the emulsified oil removal rates of the integrated Sb-doped SnO2 conductive ceramic membrane prepared in Example 1 at 20 min, 40 min and 60 min were 95.03%, 94.99% and 95.09%, respectively, and the membrane fluxes were 80.61%, 79.86% and 79.24%, respectively. 2 ), the electrochemical coupled membrane separation process significantly improved the emulsified oil removal rate and the mitigation efficiency of membrane fouling.

[0091] It can be seen from Table 2 that the doped conductive ceramic membranes prepared in Examples 1 to 3 exhibit excellent, stable water flux and high pollutant removal rate in the electrochemically coupled membrane separation reaction device, which is significantly better than the undoped integrated SnO2 ceramic membrane.

[0092] It can be seen from Tables 1 to 2 that the electrical conductivity and wastewater treatment efficiency of the integrated conductive ceramic membrane in Examples 1 to 3 of the present invention are significantly better than those of the commercial porous alumina ceramic membrane and the undoped integrated SnO2 ceramic membrane.

[0093] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing an integrated conductive ceramic film, characterized in that: The following steps are involved: A tin source, a metal dopant, an alkali reagent and an organic solvent are mixed to perform a coprecipitation reaction to obtain a precipitated product; The precipitation product is subjected to a first calcination to obtain a conductive powder; The conductive powder, the additive and the alcohol solvent are mixed and ball-milled to obtain nano conductive powder; Hydraulically pressing the nano-conductive powder to obtain a pressed tablet; The pressed sheet is subjected to a second calcination to obtain an integrated conductive ceramic membrane; The metal element in the metal dopant includes Sb, Co, Ni, La, Mn, Al or Zn.

2. The preparation method according to claim 1, characterized in that: The tin source includes SnCl4 or SnCl2; the alkaline reagent includes ammonia water.

3. The preparation method according to claim 1 or 2, characterized in that: The metal dopant includes SbCl3, CoCl2, NiCl2, LaCl3, MnCl2, AlCl3 or ZnCl2; the molar amount of the metal element in the metal dopant is 0 to 12% of the Sn element in the tin source and is not 0.

4. The preparation method according to claim 1 or 2, characterized in that: The pH of the coprecipitation reaction is 8.0-10; the temperature is 60-100° C. and the time is 2-6 hours.

5. The preparation method according to claim 1, characterized in that: The first calcination is carried out at a temperature of 500 to 800° C. and for a time of 1 to 4 hours.

6. The preparation method according to claim 1, characterized in that: The auxiliary agent includes aluminum oxide, zirconium oxide or silicon carbide; the mass of the auxiliary agent is 0-60% of the mass of the conductive powder; the time of the mixed ball milling is 1-3 hours; the pressure of the hydraulic pressing is 3-9MPa, and the stabilization time is 40-80s.

7. The preparation method according to claim 1, characterized in that: The second calcination temperature is 900-1200° C., and the time is 1-4 hours.

8. An integrated conductive ceramic membrane prepared by the preparation method according to any one of claims 1 to 7.

9. Application of the integrated conductive ceramic membrane according to claim 8 in sewage treatment, characterized in that: A cross-flow electrochemical coupled membrane separation device is used for wastewater treatment.

10. The use according to claim 9, characterized in that: The cross-flow electrochemical coupled membrane separation device comprises a raw water tank (1), a diaphragm pump (2), a power source (3), an electrolysis-filtration reactor (4), a water production tank (5), a return water regulating valve (8) and a water production regulating valve (9); the raw water tank (1), the diaphragm pump (2), the electrolysis-filtration reactor (4) and the water production tank (5) are connected in sequence; the power source (3) is connected to the electrolysis-filtration reactor (4); a conductive ceramic membrane (6) and a cathode (7) are arranged in the electrolysis-filtration reactor (4); the return water regulating valve (8) is arranged in the pipeline between the electrolysis-filtration reactor (4) and the raw water tank (1), and the water production regulating valve (9) is arranged in the pipeline between the electrolysis-filtration reactor (4) and the water production tank (5); the conductive ceramic membrane (6) is the integrated conductive ceramic membrane described in claim 8; The integrated conductive ceramic membrane serves as an anode.

Citation Information

Patent Citations

  • P-type electric-conducting Sb mixed SnO2 film and stannic oxide homogeneous pn junction containing film and preparation methods thereof

    CN102586748A

  • Preparation method of high-density high-conductivity tin antimony oxide ceramic

    CN102863210A

  • Cathode and anode built-in ceramic micro-filtration membrane reactor suitable for removing pollutant in source water

    CN107162118A

  • Perovskite type conductive ceramic membrane and preparation method and application thereof

    CN114682104A

  • Conductive ceramic membrane as well as preparation method and application thereof

    CN114716265A